2007
DOI: 10.1017/s175173110700050x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and pre-weaning growth and nutrition of cattle: long-term consequences for beef production

Abstract: Severe, chronic growth retardation of cattle early in life reduces growth potential, resulting in smaller animals at any given age. Capacity for long-term compensatory growth diminishes as the age of onset of nutritional restriction resulting in prolonged growth retardation declines. Hence, more extreme intrauterine growth retardation can result in slower growth throughout postnatal life. However, within the limits of beef production systems, neither severely restricted growth in utero nor from birth to weanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
113
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 64 publications
13
113
0
4
Order By: Relevance
“…These results suggest that hyperplasia of adipocytes, not initially visible (and hence early differentiated), plays an important role in marbling during growth (Albrecht et al, 2006). In practice, prenatal restriction (sufficient to reduce calf birth weight) has minimal effects on IMF level (Greenwood et al, 2006;Greenwood and Cafe, 2007) unlike postnatal restriction that will clearly reduce IMF level. Because fat is deposited at a lower rate than muscle growth during the first periods of postnatal life and at a greater rate than lean tissues when animals get older, the concentration of fat in muscle (i.e.…”
Section: How Might Marbling Begin?mentioning
confidence: 88%
“…These results suggest that hyperplasia of adipocytes, not initially visible (and hence early differentiated), plays an important role in marbling during growth (Albrecht et al, 2006). In practice, prenatal restriction (sufficient to reduce calf birth weight) has minimal effects on IMF level (Greenwood et al, 2006;Greenwood and Cafe, 2007) unlike postnatal restriction that will clearly reduce IMF level. Because fat is deposited at a lower rate than muscle growth during the first periods of postnatal life and at a greater rate than lean tissues when animals get older, the concentration of fat in muscle (i.e.…”
Section: How Might Marbling Begin?mentioning
confidence: 88%
“…Papstein et al (1999) have previously shown that the total number of fibres in M. longissimus was lower in twin compared with single-born beef cattle that were heavier at birth. Greenwood and Cafe (2007) reported smaller weight and cross-sectional area of longissimus muscle in response to retarded intrauterine growth, but apparent fibre number at 30 months of age was not different. Similarly, no differences in beef quality were apparent.…”
Section: Regulation Of Myogenesis and Environmental Impactmentioning
confidence: 86%
“…Taken together, these sheep and cattle studies suggest that restricted foetal growth resulting in low birth weight has similar consequences for postnatal growth rate and carcass composition as described in the pig and that this is related to myofibre number and/or muscular DNA content, whereas the effects on meat quality seem to be marginal. Species specificities in the nutritional foetal programming have been observed between ovine and bovine, due to differences in the timing of placental and foetal growth (Greenwood and Cafe, 2007) In conclusion, impaired myogenesis resulting in low skeletal myofibre and myonuclear numbers is considered one of the main reasons for the negative long-term consequences of IUGR on muscle growth.…”
Section: Regulation Of Myogenesis and Environmental Impactmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, foetal growth of AT is thought to be a critical factor contributing to adult AT mass and thus to the lifelong productivity of the offspring based on (1) a strong postnatal hypertrophy of adipocytes, which mainly increase in number during the foetal growth (Vernon, 1986) and (2) evidence for foetal programming of postnatal AT growth in bovines (Greenwood and Cafe, 2007).…”
Section: Introductionmentioning
confidence: 99%